The use intention of hospital report cards among patients in the presence or absence of patient-reported outcomes - Emmert, Martin; Schindler, Anja; Drach, Cordula; Sander, Uwe; Patzelt, Christiane; Stahmeyer, Jona; Kühnel, Elias; Lauerer, Michael; Nagel, Eckhard; Frömke, Cornelia; Schöffski, Oliver; Heppe, Laura (Health policy (Amsterdam, Netherlands), 2022)
Background: So far, the adoption of hospital report cards (HRCs) falls short of expectations. One promising strategy is to modify the content of HRCs by presenting patient-reported outcomes (PROs). Objective: To identify the key determinants influencing patients to use HRCs for hospital decision making and determine the effect of presenting PROs on HRCs on their use intention. Methods: Primary survey data were collected (5/6–2021) on a sample of 2000 randomly selected insurees from a German statutory health insurance who have undergone elective hip arthroplasty surgery. Results: Overall, 447 participants (mean age 66.56) completed the survey and were included in the analysis. Respondents rated “PROs” as most important for the hospital choice followed by “Mobility at hospital discharge” and “Confirmed diagnosis rate”. Patients generally perceive HRCs to be a good idea that makes searching for a hospital more interesting. We identified attitude and social influence as the most important determinants for using HRCs (p<.001 each). The presence of PROs on HRCs was not associated with an increased intention to use HRCs neither in our descriptive analysis (p=.593), nor in our research model (p=.763). Conclusions: Patients value PROs to be an important information for choosing a hospital. Nevertheless, health policy makers should note that presenting PROs on HRCs as a single approach is not likely to increase the use of HRCs.
CRIS-Team Scopus Importer:2022-04-15